A maternal higher-complex carbohydrate diet increases bifidobacteria and alters early life acquisition of the infant microbiome in women with gestational diabetes mellitus - Sugino, Kameron Y.; Hernandez, Teri L.; Barbour, Linda A.; Kofonow, Jennifer M.; Frank, Daniel N.; Friedman, Jacob E. (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM) is associated with considerable imbalances in intestinal microbiota that may underlie pathological conditions in both mothers and infants. To more definitively identify these alterations, we evaluated the maternal and infant gut microbiota through shotgun metagenomic analysis of a subset of stool specimens collected from a randomized, controlled trial in diet-controlled women with GDM. The women were fed either a CHOICE diet (60% complex carbohydrate/25% fat/15% protein, n=18) or a conventional diet (CONV, 40% complex carbohydrate/45% fat/15% protein, n=16) from 30 weeks’ gestation through delivery. In contrast to other published studies, we designed the study to minimize the influence of other dietary sources by providing all meals, which were eucaloric and similar in fiber content. At 30- and 37 weeks’ gestation, we collected maternal stool samples, performed fasting measurements of glucose, glycerol, insulin, free fatty acids, and triglycerides, and administered an oral glucose tolerance test (OGTT) to measure glucose clearance and insulin response. Infant stool samples were collected at 2 weeks, 2 months, and 4-5 months of age. Maternal glucose was controlled to conventional targets in both diets, with no differences in HOMA-IR. No differences in maternal alpha or beta diversity between the two diets from baseline to 37 weeks’ gestation were observed. However, women on CHOICE diet had higher levels of Bifidobacteriaceae, specifically Bifidobacterium adolescentis, compared with women on CONV. Species level taxa varied significantly with fasting glycerol, fasting glucose, and glucose AUC after OGTT challenge. Maternal diet significantly impacted patterns of infant colonization over the first 4 months of life, with CHOICE infants showing increased microbiome alpha diversity (richness), greater Clostridiaceae, and decreased Enterococcaceae over time. Overall, these results suggest that an isocaloric GDM diet containing greater complex carbohydrates with reduced fat leads to an ostensibly beneficial effect on the maternal microbiome, improved infant gut microbiome diversity, and reduced opportunistic pathogens capable of playing a role in obesity and immune system development. These results highlight the critical role maternal diet has in shaping the maternal and infant microbiome in women with GDM.